Consumer Preferences in the Selection of Muslim Fashion Products in Indonesia - Lisa Nurani; Hendri Hermawan Adinugraha (Journal of Islamic Economic and Business Research, 2022)
The development of Muslim fashion has created a community that calls itself the hijabers community, namely a group of Muslim women who wear fashionable clothes with various styles and knick-knacks for their headscarves. On the other hand, people's preferences for the importance of halal fashion are the main factors in choosing fashion products, namely convenience, product quality, and price. The research method used is library research or literature study, which contains theories relevant to the research problem. The results of this study illustrate that the trend of Muslim fashion is a positive thing because more and more people are using Muslim clothing, meaning that one of the goals of da'wah is to call for the obligation to cover the genitals to be helped by the trend. Not only that, trends and hijrah motifs play a role in determining Muslim consumer behavior in buying Muslim clothing because both are some factors that influence consumer decisions, especially personal and psychological factors.